Saccharomyces cerevisiae strains used industrially for bioethanol production - Jacobus, Ana Paula [UNESP]; Gross, Jeferson [UNESP]; Evans, John H.; Ceccato-Antonini, Sandra Regina; Gombert, Andreas Karoly (Portland Press, 2021)
Fuel ethanol is produced by the yeast Saccharomyces cerevisiae mainly from corn starch in the United States and from sugarcane sucrose in Brazil, which together manufacture ∼85% of a global yearly production of 109.8 million m3 (in 2019). While in North America genetically engineered (GE) strains account for ∼80% of the ethanol produced, including strains that express amylases and are engineered to produce higher ethanol yields; in South America, mostly (>90%) non-GE strains are used in ethanol production, primarily as starters in non-aseptic fermentation systems with cell recycling. In spite of intensive research exploring lignocellulosic ethanol (or second generation ethanol), this option still accounts for <1% of global ethanol production. In this mini-review, we describe the main aspects of fuel ethanol production, emphasizing bioprocesses operating in North America and Brazil. We list and describe the main properties of several commercial yeast products (i.e., yeast strains) that are available worldwide to bioethanol producers, including GE strains with their respective genetic modifications. We also discuss recent studies that have started to shed light on the genes and traits that are important for the persistence and dominance of yeast strains in the non-aseptic process in Brazil. While Brazilian bioethanol yeast strains originated from a historical process of domestication for sugarcane fermentation, leading to a unique group with significant economic applications, in U.S.A., guided selection, breeding and genetic engineering approaches have driven the generation of new yeast products for the market.